2012
DOI: 10.1002/smll.201201397
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hetero‐Polymer Functionalized Nanocarriers by Combining Surface‐Initiated ATRP and RAFT Polymerization

Abstract: Smart nanocarriers are created based on a bi-functional hetero-initiator for RAFT and ATRP technique, bi-functionalizing mesoporous silica nanoparticles with two polymer types. The pH-dependent behavior of PDEAEMA as the gatekeeper polymer is verified by electrokinetic measurements and a controlled release behavior is demonstrated using doxorubicin as the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 48 publications
0
52
0
Order By: Relevance
“…Huang et al 122 demonstrated that by fabricating smart bi-functionalising MSNs with two pH-dependent polymer types (poly(2-diethylaminoethyl methacrylate) (PDEAEMA)), controlled release of doxorubicin was possible.…”
Section: Currently Available Drug Delivery Systemsmentioning
confidence: 99%
“…Huang et al 122 demonstrated that by fabricating smart bi-functionalising MSNs with two pH-dependent polymer types (poly(2-diethylaminoethyl methacrylate) (PDEAEMA)), controlled release of doxorubicin was possible.…”
Section: Currently Available Drug Delivery Systemsmentioning
confidence: 99%
“…Thus, it is reasonable to presume that, after drying, the dendront ightly congregates on the surface of the material, thus preventing penetration of nitrogen. [42,43] Therefore, the functionalised MSNs-G3 materiali nherits the mesoporouss tructure of the MSNs, and because the dendrons are not stiff and static entities, the material would still preserve the potential to act as ad rug carrier by using the void mesopores.…”
Section: Dendrong Rafting To Mesoporous Silicamentioning
confidence: 99%
“…24 Since then, many MCM-41-based nanoparticles have been developed, most of them including different molecules attached on MSNs surface acting as specific stimuli-responsive gates, thus allowing "zero premature release" and delivery only upon application of a specific stimulus. 25,26,27 These concepts have allowed researchers to design on-command delivery carriers that can be triggered by stimuli such as changes in pH, [28][29][30][31][32][33][34][35][36][37] light, 38-45 temperature [46][47][48][49][50] or ultrasound, 51,52 and the presence of given enzymes 53,54 or of complementary oligonucleotides. [55][56][57][58] In particular, the enzymatic degradation of gatekeepers in MSNs represents an interesting way to achieve controlled release of drugs in target cells.…”
Section: Introductionmentioning
confidence: 99%